Healthful school environment practices in Sibulan District, Negros Oriental and their implications to the school health program - Lapez, Fe (Centeno) (s.n.], 1972)
This study identified the healthful school environment practices in Sibulan District, Negros Oriental. It was conducted to find out the practices of school personnel and pupils in the matter of providing a healthful school environment.